Increased Online Gaming Addiction Corresponds to Reduced Social Interaction in Adolescents - Rizki, Reza; Rahman, Irpan Ali; Arofiati, Fitri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Online gaming addiction is characterized by excessive and uncontrolled gaming behavior, driven by persistent urges to play and difficulty regulating duration and frequency. This behavioral pattern has the potential to affect various aspects of adolescent functioning, particularly their social interaction, which includes relationships between individuals, between individuals and groups, and among groups. The purpose of this study was to examine the relationship between online gaming addiction and social interaction among adolescents. A quantitative cross‑sectional design was applied, involving 42 adolescents selected through purposive sampling. Data were collected using standardized questionnaires assessing the level of online gaming addiction and the quality of social interaction. Statistical analysis was performed using the Rank‑Spearman test. The results showed that 59.5% of participants were categorized as having a high level of online gaming addiction, and 54.5% demonstrated poor social interaction. Statistical testing revealed a significant relationship between the two variables (p < 0.005). In conclusion, the study demonstrates a clear inverse association: higher levels of online gaming addiction are linked to lower quality of social interaction among adolescents, indicating that excessive gaming may hinder adolescents’ ability to engage effectively in social relationships.Keywords: online gaming addiction; social interaction; adolescents